Monitoring the impact of COVID-19 in Myanmar: Agricultural equipment retailers - November 2020 survey round - Takeshima, Hiroyuki; Zone, Phoo Pye; Masias, Ian (International Food Policy Research Institute, 2020)
Agricultural equipment retailers (ER) play an essential role in meeting the demand from farmers for the provision of a diverse set of machines and equipment at affordable prices which are needed for the heterogeneous agricultural production environments in Myanmar. The business operations of ERs can be particularly sensitive to bottlenecks in trade flows and to internal logistical disruptions that affect their inventory management. Given their close linkages with mechanization service providers, the financial and supply challenges that ERs face can have repercussions on the provision of mechanization services as well.